Effects of a competitive wrestling season on body composition, endocrine markers, and anaerobic exercise performance in NCAA collegiate wrestlers - Ratamess, N. A.; Hoffman, J. R.; Kraemer, W. J.; Ross, R. E.; Tranchina, C. P.; Rashti, S. L.; Kelly, N. A.; Vingren, J. L.; Kang, J.; Faigenbaum, A. D. (European Journal of Applied Physiology, 2013)
Few data exist examining the body composition, endocrine, and anaerobic exercise performance changes over a competitive wrestling season. Eighteen NCAA wrestlers were tested for endocrine markers, body composition, hydration, grip strength, and power on four occasions: prior to pre-season training (T1); after pre-season training 3 days prior to the first seasonal meet (T2); mid-season one day prior to a meet (T3); and at the end of the season 2-3 days following the last meet (T4). Body mass, percent body fat (BF %), and fat mass were significantly lower (P < 0.05) at T2 and T3 compared to T1 but were not different between T1 and T4. Lean body mass was significantly reduced at T2 only. Urine specific gravity was significantly elevated at T3 compared to T1, T2, and T4. Resting cortisol concentrations did not change but resting testosterone concentrations were significantly reduced at T2, T3, and T4. Maximal grip strength was significantly reduced at T2. Vertical jump peak power was significantly reduced at T2, T3, and T4. Wingate peak power was significantly reduced at T2 and T3. However, Wingate average power and total work did not significantly change. Fatigue rate during the Wingate test was significantly improved at T2, T3, and T4 compared to T1. In conclusion, body mass, BF %, and measures of peak force and power were reduced for most of the competitive wrestling season. Competitive wrestling reduces resting total testosterone concentrations throughout the entire season.